How "Madame Bovary" is written (Flaubert and his narrator). Part 2 - Vasily Tolmatchoff (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. 3, Filologii͡a, 2022)
In a paper, written in polemics with mythology of the Flauberian studies of XX, particularly of the Soviet origin (the so-called realism or new realism, objectivism, impersonality, rationality of Flaubertian manner in “Madame Bovary”, identification of the author and his skills with the narrator, etc.), a figure of the narrator in this novel is discussed in full detail for the first time. This figure, a concrete person and a creator of narrative, is corresponded with Flaubert on various levels (biographical, gender, psychological, rationally creative, intertextual, subconscious) as well as with the characters (including the narrator on his own, his self-reflexion, psychological and psychic complexes, aims, methods and stylistics of narration). Antifeminine dimension of the narrative. «We» of the narrative is interpreted as a controversial sum of “I”, “non-I”, “other I-ies”, shadow projections of “I”, theatrical metamorphoses of “I”. In context of a special position of the narrator bourgeoisness, literatureness of the social consciousness, romanticism, palimpsest of the narrative, the double ending, and also the motives of story-telling and justification of creative efforts are analyzed. Symbolically the main events of the narrator’s world are death and positioning of himself as an inventor of fictions (“the lies”), a highly personal narrative the roots of which are in his school childhood, his mania of additional details and of endless improvement of his text. The narrator as a madman and an author of the madman’s diaries. The characters of the novel as artists. A study of the poetics of repetitions, mirror scenes, colours (blue, red, green), erotics, nature, historical details permits V. M. Tolmatchoff to introduce a rather new interpretation of Flaubert’s work as belonging to romanticism (partially baroqian, partially classical). The paper reconstructs chronology of events, age of the characters and poses a problem of Flaubert as inventor, of a meaning of non-correspondence in his novel between purely fictional time-space and strict historical details.